An annotated checklist and a family key to the pseudoscorpion fauna (Arachnida: Pseudoscorpiones) of Sri Lanka - Batuwita, Sudesh; Benjamin, Suresh P. (Zootaxa, 2014)
Sri Lanka is part of the Western Ghats & Sri Lanka biodiversity hotspot. Thus, the conservation of Sri Lanka’s unique biodiversity is crucial. The current study is part of an ongoing survey of pseudoscorpion fauna of Sri Lanka. We carried out an island-wide survey of pseudoscorpions using a range of collection methods to sample a diverse set of habitats around the country. This produced 32 species, four of which might be new to science, belonging to 25 genera. The family Cheiridiidae was discovered on the island for the first time. One new combination, Indogarypus ceylonicus (Beier, 1973) comb. nov., is proposed. Out of the 47 species now recorded, 20 (43 %) are potentially endemic to Sri Lanka. We provide a checklist of all known species, document their distribution and give a key to the families.